2022
DOI: 10.1016/j.numecd.2021.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a diet based on the Dietary Guidelines on vascular health and TMAO in women with cardiometabolic risk factors

Abstract: Background and aims: Recent evidence links trimethylamine oxide (TMAO) to endothelial dysfunction, an early indicator of cardiovascular disease. We aimed to determine whether short-term consumption of a diet patterned after the 2010 Dietary Guidelines for Americans (DGA) would affect endothelial function, plasma TMAO concentrations, and cardiovascular disease risk, differently than a typical American Diet (TAD). Methods and results: An 8-wk controlled feeding trial was conducted in overweight/obese women pre-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…However, other explanation is possible and warrants further investigations since a study published while this paper was under review observed no TMAO change after a 2010 DGA-pattern diet. [57] Our results related to traditional CVD risk factors concur in part with three absence-of-superiority reporting that showed i) no blood pressure increase, [9] and ii) no triglyceride increase after pork intake. [58,59] Furthermore, the strong association between baseline TMAO of participants and their subsequent TMAO-response to both proteins, highlights that further investigation may reveal if individual microbiota-associated TMAOphenotypes may be used as an atherosclerosis risk-assessment marker or to customize dietary manipulations for reducing chronic disease burden.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, other explanation is possible and warrants further investigations since a study published while this paper was under review observed no TMAO change after a 2010 DGA-pattern diet. [57] Our results related to traditional CVD risk factors concur in part with three absence-of-superiority reporting that showed i) no blood pressure increase, [9] and ii) no triglyceride increase after pork intake. [58,59] Furthermore, the strong association between baseline TMAO of participants and their subsequent TMAO-response to both proteins, highlights that further investigation may reveal if individual microbiota-associated TMAOphenotypes may be used as an atherosclerosis risk-assessment marker or to customize dietary manipulations for reducing chronic disease burden.…”
Section: Discussionsupporting
confidence: 89%
“…However, other explanation is possible and warrants further investigations since a study published while this paper was under review observed no TMAO change after a 2010 DGA‐pattern diet. [ 57 ]…”
Section: Discussionmentioning
confidence: 99%
“…Overweight/obese women prescreened for insulin resistance and/or dyslipidemia a Eight-week controlled feeding trial Did not improve endothelial function or reduce plasma TMAO [159] Seventy-eight patients that participated in the atrial fibrillation (AF) risk study b Two-week event recorder at baseline and 1-year follow-up…”
Section: Health Condition Duration Of Study Impression Referencesmentioning
confidence: 99%
“…Circulating concentrations of TMAO have drawn attention as a potential mediator or biomarker of diseases such as obesity, cardiovascular disease, diabetes, kidney disease, and cancer [88][89][90][91][92][93][94]. Various randomized controlled feeding trials and observational cross-sectional studies in which diet was assessed through FFQs or diet records report conflicting results on TMAO concentrations and associations with unfavorable disease outcomes in humans [95][96][97][98][99][100][101][102][103][104][105]. The conflicts can likely be attributed to differences in study designs and characteristics and metabolic profiles of the study population.…”
Section: Trimethylamine N-oxide Increased In Response To a Higher Bee...mentioning
confidence: 99%